Improving The Students’ Speaking Confidence by Online Learning - Imam Suseno; Tarmizi Rasul; Supadi Supadi (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2022)
There are some problems being faced by English teachers especially at SMK Kesuma Bangsa Depok to teach English. Enriching their students’ vocabulary and teaching parts of speech especially tenses are the two most challenging efforts. The appropriate methods to teach both of them were an Oral Questioning and Guiding in L1 (OQIGIL) methods. This study used an online action research implemented in SMK Kesuma Bangsa Depok grade XII, taking three months started in October to December 2021. This study involved 54 students of the Office Management Automation Program (OTKP) selected by simple random sampling. There were some activities to do during this action reseach cycle: 1) an action planning setting, 2) an action, 3) an observation, an evaluation, and 4) a reflection. The result of this study show that the OQIGIL method used in this classroom action research has made the students speak English confidently and appropriately since the average of the students’ English speaking scores are 74,54 at the first cycle and becomes 74,54 at the second cycles and the average of the third cycles is 79,63. The data indicate that there are four students (7%) at the first cycle, 23 students (43%) at the second cycles, and 33 students (61,11 %) at the third cycles to speak English confidently since the students are challenged to think English appropriately from the English materials directed in L1 by their English teachers and group captains during online learning